The Identification of Verbal and Non Verbal Expressions Used By Waiter and Waitress in Serving Guest at Puri Bagus Hotel - Amertadana, Ketut Alit (Jurnal Penelitian Mahasiswa Indonesia, 2024)
This research had been done at Puri Bagus Resort. This research had two purpose, there were: (1) Revealing the sequence of service which are implemented at Puri Bagus Hotel and (2) Identifying the verbal and Non Verbal expressions of waiters and waitress at Saraswati Restaurant based on sequence of service they used. The objects of the research were sequence of service which are implemented at Puri Bagus Hotel and verbal and non verbal expressions were used by the waiter and waitress at Saraswati Restaurant based on sequences of service they used. Whereas subjects this study were waiter and waitress at Saraswati Restaurant. Collecting data used non-participant observation. Then analyze that data by descriptive method. The result of this research is: (1) There are 5 sequences of service implemented by Puri Bagus staff. And (2) The waiters and waitress at Saraswati Restaurant use a little different verbal expressions in serving guest and they use non-verbal expressions such as : eye contact, facial expressions, gesture and space.